Experimental investigation on boiling heat transfer enhanced by gradient aperture porous copper. (5th June 2021) - Ma, Yahui; Huang, Congliang; Wang, Xiaodong
Highlights: Gradient aperture porous Cu was prepared and used in pool boiling heat transfer. Gradient aperture porous Cu can reduce ONB and increase HTC. Large SSA and steam accumulation affect the boiling heat transfer of porous Cu. Gradient aperture structure helps fluid replenishment and vapor escape in boiling. Abstract: To ensure the working stability of electronics, highly-efficient heat dissipation technology such as pool boiling is attracting more and more attention. The three-dimensional porous surface used in pool boiling enhancement will be subject to the vapor leaving resistance, which will lead to steam accumulation and thus weaken the pool boiling heat transfer performance. To facilitate the vapor releasement and also the liquid replenishment in the three-dimensional porous surface, we developed multi-layer gradient aperture open-cell porous copper in this work. Then, the pool boiling curves and the corresponding bubble dynamics of these porous copper samples were experimentally investigated. Results show that the onset of nucleate boiling (ONB) of a 4-layer gradient sample (about 0.9 ℃) is only about 8.3% that of the smooth surface (about 12 ℃), and the maximum heat transfer coefficient (about 8.2 × 10 4 W/m 2 ·K) is about 8 times higher than that of the smooth surface, resulting from the porous structure which could disturb the flow field and provide massive nucleation sites. We also found that the bubble departure diameter of the 4-layer sample is almost 50% times smaller than that of the smooth surface while the frequency is 2 times higher. This phenomenon is due to the gradient aperture structure which could match the different pore-aperture requirements of both vapor escape and liquid replenishment. Considering the simple fabrication and excellent pool boiling performance, we conclude that the gradient aperture porous copper could provide an effective way for boiling heat transfer enhancement.